MCM4 expression is associated with high-grade histology, tumor progression and poor prognosis in urothelial carcinoma - Go Kobayashi; Tetsutaro Hayashi; Kazuhiro Sentani; Naohiro Uraoka; Takafumi Fukui; Aya Kido; Narutaka Katsuya; Akira Ishikawa; Takashi Babasaki; Yohei Sekino; Hiroyuki Nose; Koji Arihiro; et al. (BMC, 2023)
Abstract Background We previously reported Minichromosome maintenance 4 (MCM4) overexpression in gastric cancer. However, the clinicopathological significance of MCM4 in urothelial carcinoma (UC) has not been investigated. To clarify the clinicopathological significance of MCM4 in UC, we investigated MCM4 expression with immunohistochemistry (IHC). Methods We analyzed the expression and distribution of MCM4 in 124 upper tract urothelial carcinoma (UTUC) samples by IHC. Additionally, using 108 urine samples, we analyzed MCM4 Immunocytochemistry (ICC) expression in urine cytology. Results In normal urothelium, MCM4 expression was weak or absent. Meanwhile, the strong nuclear expression of MCM4 was observed in UTUC tissues, and it was detected in 77 (62%) of a total of 124 UTUC cases. MCM4-positive UTUC cases were associated with nodular/flat morphology, high grade, high T stage, and poor prognosis. Moreover, MCM4 expression was significantly higher in the invasive front than in the tumor surface. Similar results were also obtained in TCGA bladder cancer cohort. Additionally, MCM4 expression was associated with high expression of Ki-67, HER2, EGFR, and p53 in UTUC. Among representative cancer-related molecules, MCM4 had an independent predictive value for progression-free survival and high-grade UC. ICC for MCM4 was also performed on urine cytology slides and showed that the nuclear expression of MCM4 was more frequently found in UC cells than in non-neoplastic cells. The diagnostic accuracy of urine cytology was improved by combining MCM4 immunostaining with cytology. Conclusion These results suggest that MCM4 might be a useful predictive biomarker for high-grade histology, tumor progression and poor prognosis in UC. Moreover, ICC for MCM4 might be helpful for UC detection as additional markers in the cytomorphology-based diagnosis.